CHARACTERISTIC OF REPRODUCTIVE AGE WOMEN LIVING WITH HIV/AIDS IN VICTORY PLUS FOUNDATION, YOGYAKARTA, INDONESIA - Rukmi, Dwi Kartika; Sari, Ike Wuri Winahyu; Lutfiyati, Afi (Jurnal Keperawatan Respati Yogyakarta, 2020)
Around 50% of people living with HIV/AIDS worldwide are women, and women of reproductive age are the group of women who are most infected by HIV/AIDS. Indonesia is a country that has increased the number of people with HIV/AIDS up to three folded since 2009-2014 and the number of women infected with HIV/AIDS also continues to increase. This study aims to look at the characteristics of women living with HIV / AIDS (WLWHA) in Victory Plus who are of reproductive age. This study is descriptive research with a cross-sectional approach that was conducted on 288 women with HIV / AIDS taken by purposive sampling who met the inclusion criteria in Victory Plus Foundation, Yogyakarta. Data were taken by questionnaire in March ? June 2019 and processed by univariate analysis according to the data. The results showed that respondents 100% underwent ART, they are 35.42 ± 6.91 years old, suffered HIV for 4.06± 3.21 years, and have a length of ART duration for 3.74±3.11 years. Most of WLWHA are Muslims (89,9%), Javanese (94,4%), married women (52,8%), senior high school educated (46,5%), housewives (68,8%), have living children (80,6%), have no child with HIV(87,5%), adherence on ART(85,4%), have steady sex partner (75,3%), disclosed their HIV status to their sexual partner (50,7%), disclosed their HIV status to others (50,7%), and having better health perception (73,3%). The conclusion that the characteristics of respondents are mostly Muslim, have a high school education background, work as a housewife, are married, have live children, have no children with HIV, are on ART, open to sexual partners, open to other than sexual partners and have improved health perception.